Analysis for global characteristics of Lyapunov exponents in vehicle plane motion system - Meng, Fanyu; Shi, Shuming; Zhang, Boshi; Bai, Minghui; Lin, Nan (Scientific reports, 2022)
In the field of vehicle system dynamics, it is significant to propose an appropriate quantitative indicator for system stability or dynamics characteristics. Lyapunov exponents method is an excellent quantitative indicator for analysing nonlinear system characteristics. It was used to studied the stable region of nonlinear vehicle plane motion system. However, the effect of Lyapunov exponents method in revealing the global dynamics characteristics has not been fully studied. Aiming at this key problem, this paper analyses the global characteristics of Lyapunov exponents with different degrees of freedom nonlinear models. The results show that Lyapunov exponents can well reflect the global layer characteristics for vehicle system. However, the value characteristic under different DOF models is not unified. The research and analysis in this paper supplement the quantitative analysis theory for vehicle system dynamics.